Optimal sampling designs for large-scale fishery sample surveys in Greece - BAZIGOS, G.; KAVADAS, S. (Mediterranean Marine Science, 2007)
The paper presents the quality problem of fishery statistics produced by the conducted land-based and sea-going, large scale sample surveys of the survey programme of the Institute of Marine Biological Resources of the Hellenic Centre for Marine Research (IMBR/HCMR) in Greece, and the optimality strategies developed in their sampling designs for the maximization of precision of the calculated sample estimates for a given cost of sampling. The optimality problems of the sampling designs of the individual large scale sample surveys are described, and the optimality solutions developed under the sampling variance structure are explained. The paper deals with the optimization of the following three large scale sample surveys: biological sample survey of commercial landings (BSCL), experimental fishing sample survey (EFSS), and commercial landings and effort sample survey (CLES).